Configural analysis of dry-land strength and front crawl performance in adolescents - Gao, Tianyi; Shen, Jiawen; Tang, Baojie; Wu, Xinyuan; Shi, Yifan; Huang, Bo (Frontiers in Physiology, 2025)
IntroductionDry-land strength capacities play a crucial role in competitive swimming, especially in short-distance events where explosive force and coordination are decisive. However, most research has focused on isolated variables rather than exploring how combinations of strength attributes jointly influence performance. Competitive swimming performance is influenced by multiple interacting physical attributes, yet the specific combinations of dry-land strength capacities that contribute to short-distance front crawl performance in adolescents remain unclear.MethodsTo address this gap, this study employs fuzzy-set Qualitative Comparative Analysis (fsQCA) to investigate the configurational relationships between dry-land strength parameters and 50-m front crawl swimming performance among adolescent competitive swimmers. Eighty-five adolescent competitive swimmers (n = 85; age: 15.0 ± 1.5 years; weight: 61.5 ± 9.6 kg) were categorized into three groups based on competition scores and underwent seven physical assessments, including deep squats, pull-ups, grip strength tests, medicine ball throws, progressive plank, and vertical jumps.ResultsUsing fsQCA 3.0 software, configuration analysis revealed six significant causal configurations explaining 72.7% of high-performance cases. Configurations S1a/S1b identified core conditions in deep squats, pull-ups, and grip strength, while S2a/S2b highlighted bench press and vertical jumps for enhancing stroke efficiency and start/turn acceleration. The S3/S4 configurations demonstrated unique contributions from whole-body coordination and vertical explosiveness, respectively.DiscussionMultifactor synergy is key to improving swimming performance, and different athletes may need an individualized training focus. Coaches should develop a training plan based on the specific needs of the athletes to maximize their potential.